2006
DOI: 10.1111/j.0014-3820.2006.tb01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Persistence of Phenotypic Integration: Influence of Developmental and Functional Relationships on Complex Trait Evolution

Abstract: Abstract. Examination of historical persistence of integration patterns provides an important insight into understanding the origin and evolution of complex traits. Specifically, the distinct effects of developmental and functional integration on the evolution of complex traits are often overlooked. Because patterns of functional integration are commonly shaped by selection exerted by the external environment, whereas patterns of developmental integration can be determined by relatively environment-independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 59 publications
(40 reference statements)
4
57
0
2
Order By: Relevance
“…Analyses of covariation in the asymmetries of landmark configurations thus can be used to infer whether such developmental interactions exist (Section 6). This approach has been applied in a growing number of studies [11,16,44,49,51,56,59,63,67,72,74,75,78,79,82,139,[167][168][169][170][171][172][173][174].…”
Section: Fluctuating Asymmetrymentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of covariation in the asymmetries of landmark configurations thus can be used to infer whether such developmental interactions exist (Section 6). This approach has been applied in a growing number of studies [11,16,44,49,51,56,59,63,67,72,74,75,78,79,82,139,[167][168][169][170][171][172][173][174].…”
Section: Fluctuating Asymmetrymentioning
confidence: 99%
“…Many studies have found matrix correlations between covariance matrices for fluctuating asymmetry and individual variation that are statistically significant, but of rather variable strengths [11,16,44,49,55,56,67,72,79,82,97,106,119,139,[167][168][169]172,173,177,358]. A few studies have reported a mix of significant and non-significant results for analyses of multiple samples or structures [54,75,120,174], and some other studies found only non-significant test results [13,42,73,78].…”
Section: Developmental Instability Versus Canalization: One or More Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Because fluctuating asymmetry originates from random variation in developmental processes, the asymmetries of different traits are correlated only if there are direct interactions between developmental pathways that produce the traits [46,47]. This approach has been applied in a broad range of animal systems [10,[12][13][14][15]27,36,37,[48][49][50][51][52][53][54][55]. Whereas this reasoning applies widely to motile organisms, including most animals, caution is necessary in applying it to sessile organisms like most plants, where a part of fluctuating asymmetry may be due to plastic responses to heterogeneity in microenvironmental factors [25,56].…”
Section: (B) Developmental Integrationmentioning
confidence: 99%
“…Certain combinations of traits rarely occur randomly: they may be selected for their coordinated function or have a common genetic basis such as pleiotropy (Mclellan, 2005). Trait integration produced by a shared genetic basis is usually independent of the environment, whereas integration caused by functional association may vary across environments (Young and Badyaev, 2006). However, it cannot be concluded that traits evolve independently if only residual correlation is detected in a single experiment.…”
Section: Discussionmentioning
confidence: 99%